System dynamics modelling of mixed recycling mode based on contract: a case study of online and offline recycling of E-waste in China. Issue 3 (3rd May 2020) - Miao, Shidi; Liu, Di; Ma, Junfeng; Tian, Feng
ABSTRACT: As the pace of global sustainable economic development accelerates, increasing attention has been brought to the reutilization of waste electronic resources (E-waste). As the leading manufacturer and consumer of electronic products, China has now become the largest producer of E-waste around the world. Considering the current state of recycling mode in China, Huawei Technologies Co. Ltd. (Huawei) took the lead in implementing a blended operation model of manufacturer-led recycling model (offline recycling, OffR) and retailer-led recycling model (online recycling, OnR). In order for the improvement of recycling efficiency for Huawei and other telecommunication companies, this paper constructs a closed-loop network model of mixed recycling (MR) between manufacturers and retailers based on contract, where manufacturers and retailers jointly recycle E-waste for the provision of E-waste to manufacturers for remanufacturing. In this paper, the MR model is compared against the OffR model and OnR model to evaluate the recycling allocation mechanism run by both manufacturer and retailer and then a contract-based, closed-loop network model of mixed recycling between manufacturers and retailers is developed on the basis of obtaining the optimal MR model. By means of simulation analysis, the optimal recycling allocation ratio between manufacturer and retailer is determined. The results obtained from this study are expected to help manufacturers and retailers with effective negotiation and cooperation, so as to improve the efficiency of E-waste recycling while promoting sustainable development and reducing the economic losses caused by price competition to the minimum. This research contributes to not only the waste management studies but also the recycling of E-waste in China and other countries.